Demographics and the Placebo Response in the REPLENISH TRIAL: A Study of Vasomotor Symptoms [16OP]. (May 2018) - Constantine, Ginger; Graham, Shelli; Bernick, Brian; Archer, David
Abstract : INTRODUCTION: High placebo responses (up to 61%) are reported in studies evaluating therapeutic agents for vasomotor symptoms (VMS). Placebo response rates by subgroups from a recently completed positive trial of an investigational combination of 17β-estradiol and progesterone capsule (TX-001HR) are presented. METHODS: REPLENISH was a phase 3, randomized, double-blind, placebo-controlled trial that evaluated safety/efficacy of TX-001HR in postmenopausal women, who had ≥50 moderate to severe hot flushes at baseline. 767 women received one of four TX-001HR daily doses or placebo; frequency and severity of VMS at baseline and weeks 4 and 12 were recorded by diary. Secondary endpoints were responder analyses and menopause-specific quality of life (MENQOL) questionnaire. Subgroup analysis of efficacy was performed on demographics. RESULTS: The placebo response rate was high (55%). Significant differences were observed in the placebo response rates between White (51%) and African American (65%) women at 12 weeks ( P =.049). Mean age was similar; more African American women had BMI≥30 kg/m 2 (32.4%) vs White (18.7%). More African American women were current smokers than White (41.5% vs 17.6%). Significant differences in responders (≥50% and ≥75%) and the MENQOL Vasomotor Domain were observed for all groups compared to placebo in the White population; no differences noted in African Americans due to high placebo rate. Baseline estradiol levels and compliance rates for African American and White women were similar. CONCLUSION: Large placebo responses occurred and more frequently in African Americans. Understanding factors that contribute to placebo responses are important in designing and assessing the efficacy of medications in clinical trials.